ENHANCING REFUGEE HEALTH AND RIGHTS THROUGH SCREENING: LEGAL AND PUBLIC HEALTH PERSPECTIVES IN INDONESIA - Kusumo, Ayub Torry Satriyo; Damayanti, Kusmadewi Eka (Universitas Syiah Kuala, 2025)
Health has become a primary concern due to the increased vulnerability of refugees to disease, especially in refugee settings where risks of illness are heightened. These environments often expose refugees to higher health threats and can lead to unintentional violations of their basic rights. However, healthcare for refugees has not been adequately addressed, largely due to legal gaps in Indonesias refugee handling policies. This study emphasizes the importance of implementing health and malnutrition screening in refugee settings from both sovereignty and public health perspectives. The research is a literature review of peer-reviewed open-access articles sourced from PubMed and Scopus, using keywords such as malnutrition and refugee setting. Additionally, legal documents relevant to refugee rights, including the 1951 Refugee Convention, international agreements, Presidential Decree 125/2016 on handling refugees from abroad, and other pertinent legal texts, were analyzed to provide a legal framework for the findings. The study reveals that healthcare services in refugee settings are limited and often inaccessible. To address this, it proposes that health and malnutrition screening serve as initial steps to safeguard refugees right to health, grounded in the sovereignty principle. Despite Indonesias non-participation in the 1951 Convention and the 1967 Protocol, protecting public health by preventing disease transmission from refugees aligns with national sovereignty. Therefore, Indonesia, even without formal refugee status recognition, should prioritize health screening and adhere to international Minimum Standards and the principle of National Treatment to ensure the protection of both refugees and the broader community.